Megosztott társadalom: Mexikó és a Spanyol polgárháború, 1936–1939 - Sánchez Andrés, Agustin (Acta Scientiarum Socialium, 2015)
A Divided Society: Mexico and the Spanish Civil War, 1936–1939 The Spanish Civil War caused the polarization of Mexican society during the conflict. The government of general Lázaro Cárdenas and the leftist parties and unions supported the Spanish Republic in the League of Nations, and provided them weapons to break the blockade. The conservative opposition sympathized with the military rebels and supported their nationalist and catholic aspirations. This situation caused a paper war in the Mexican press between the conservative newspapers, like Excelsior and El Universal, and the official press.
Keywords: Spanish Civil War; Cardenism; MexicoÂ´s Foreign Policy; League of Nations